Causal associations of iron status and back pain risk: A Mendelian randomization study - Tang, Yidan; Wu, Jiahui; Xu, Mingzhe; Zhu, Tao; Sun, Yalan; Chen, Hai; Wu, Lining; Chen, Chan (Frontiers in Nutrition, 2022)
Background: Observational studies have previously suggested a link between iron status makers and back pain. We conducted a two-sample Mendelian randomization (MR) study to determine the putative causal relationship between systemic iron status and back pain. Methods: In this MR study, a genome-wide association study (GWAS) involving 48 972 individuals was used to identify genetic instruments highly associated with systemic iron status. The outcome data (back pain) were derived from the Neale Lab consortium's summary data from the UK Biobank (85,221 cases and 336,650 controls). With the inverse variance weighted (IVW) method as the main analysis, conservative analyses (selecting SNPs with concordant change of iron status biomarkers) and liberal analyses (selecting SNPs with genome-wide significant association with each iron status biomarker) were carried out. For sensitivity analyses, the MR-Egger, MR-Egger intercept, weighted median, weighted mode, and MR based on a Bayesian model averaging approaches were used. The Cochran's Q-test was used to detect heterogeneity. Results: Back pain was associated with genetically instrumented serum iron (OR = 1.01; 95%CI = 1.00-1.02, p = 0.01), ferritin (OR = 1.02; 95%CI = 1.00–1.04, p = 0.02), and transferrin saturation (OR = 1.01; 95%CI = 1.00–1.01, p = 0.01). Furthermore, there was no evidence of a link between transferrin and the risk of back pain (OR = 0.99, 95%CI = 0.98–1.00, p = 0.08). The sensitivity analyses and Cochran's Q-test indicated that no pleiotropy or heterogeneity was detected (all p > 0.05). Conclusion: We provided potential genetic evidences for the causal associations of iron status with increased incidence of back pain. However, the evidences were weakened due to the low power. Further larger MR studies or RCTs are needed to investigate small effects.